FACTORS AFFECTING EMPLOYEE PERFORMANCE IMPROVEMENT ON FINANCE COMPANIES - Riyadi, Indra; Setiawan, Margono; Ratnawati, Kusuma (Jurnal Aplikasi Manajemen, 2018)
The purpose of this study is to examine and determine the factors that can affect employee performance improvement in finance companies. The research method used is a quantitative approach. Data were analyzed by Partial Least Square (PLS) statistic tool. This research was conducted at PT. Mandiri Tunas Finance Malang Branch and Pasuruan Satellite. The population in this study were all permanent employees, amounting to 82 people. Furthermore, the entire population became the respondents so that this research used the census method in the sample determination. Based on the result of the research, it can be concluded that the factors that can improve employee performance in finance company are motivation, especially motivation that comes from within the employees themselves (intrinsic motivation) and organizational culture, while leadership can influence the improvement of employee performance if mediated by work motivation. Some suggestions that can be put forward to improve employee performance in finance companies are building employee work motivation, by holding special education program for employees in order to get promotion, continuous training, provides a challenging task, and adequate working facilities; Create a good organizational culture so that it can help employees to make it easier to carry out their work; Recruiting employees who have work experience ranging from 5 years with educational background is a bachelor.